The efficacy and safety of JAK inhibitors for alopecia areata: A systematic review and meta-analysis of prospective studies - Yan, Diqin; Fan, Huaying; Chen, Min; Xia, Lin; Wang, Simin; Dong, Wenliang; Wang, Qian; Niu, Suping; Rao, Huiying; Chen, Liming; Nie, Xiaoyan; Fang, Yi (Frontiers in Pharmacology, 2022)
Background: Due to the lack of comprehensive evidence based on prospective studies, the efficacy and safety of Janus Kinase (JAK) inhibitors (including tofacitinib, ruxolitinib, baricitinib, ritlecitinib and brepocitinib) for alopecia areata (AA) are yet to be proved. Methods: The systematic review and meta-analysis was performed pursuant to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline and registered on PROSPERO (CRD42022303007). Results: Fourteen prospective studies (5 RCTs and 9 non-RCTs), enrolling a total of 1845 patients with AA, were included for quantitative analysis. In RCTs, oral JAK inhibitors resulted in higher good response rate compared with control (RR: 6.86, 95% CI: 2.91 to 16.16); topical JAK inhibitors did not show any difference compared with control (RR: 1.00, 95% CI: 0.31 to 3.18). In non-RCTs, the pooled rate of good response to oral, topical and sublingual JAK inhibitors were 63% (95% CI: 44% to 80%), 28% (95% CI: 1% to 72%) and 11% (95% CI: 1% to 29%), respectively. The pooled recurrence rate in patients treated with JAK inhibitors was 54% (95% CI: 39% to 69%), mainly due to the withdrawal of JAK inhibitors. In RCTs, no difference was found in the risk of experiencing most kind of adverse events; in non-RCTs, the reported adverse events with high incidence rate were mostly mild and manageable. Conclusions: JAK inhibitors are efficacious and generally well-tolerated in treating AA with oral administration, whereas topical or sublingual administration lacks efficacy. Subgroup analyses indicate that baricitinib, ritlecitinib and brepocitinib seem to have equal efficacy for AA in RCTs; ruxolitinib (vs. tofacitinib) and AA (vs. AT/AU) are associated with better efficacy outcomes in non-RCT. Due to the high recurrence rate after withdrawal of JAK inhibitors, continuous treatment should be considered to maintain efficacy.